Digital youth the role of media in development - Subrahmanyam, Kaveri; Smahel, David; SpringerLink (Online service). (New York Springer, 2011)
Youth around the world are fittingly described as digital natives because of their comfort and skill with technological hardware and content. Recent studies indicate that an overwhelming majority of children and teenagers use the Internet, cell phones, and other mobile devices. Equipped with familiarity and unprecedented access, it is no wonder that adolescents consume, create, and share copious amounts of content. But is there a cost? Digital Youth: The Role of Media in Development recognizes the important role of digital tools in the lives of teenagers and presents both the risks and benefits of these new interactive technologies. From social networking to instant messaging to text messaging, the authors create an informative and relevant guidebook that goes beyond description to include developmental theory and implications. Also woven throughout the book is an international sensitivity and understanding that clarifies how, despite the widespread popularity of digital communication, technology use varies between groups globally. Other specific topics addressed include: Sexuality on the Internet. Online identity and self-presentation. Morality, ethics, and civic engagement. Technology and health. Violence, cyberbullying, and victimization. Excessive Internet use and addictive behavior. This comprehensive volume is a must-have reference for researchers, clinicians, and graduate students across such disciplines as developmental/clinical child/school psychology, social psychology, media psychology, medical and allied health professions, education, and social work.
Preface -- Acknowledgements -- About the Authors -- Adolescents' Digital Worlds: An Introduction -- Connecting Online Behavior to Adolescent Development: A Theoretical Framework -- Sexuality on the Internet: Sexual Exploration, Cybersex, and Pornography -- Constructing Identity Online: Identity Exploration and Self-presentation -- Intimacy and the Internet: Relationships with Friends, Romantic partners, and Family Members -- Digital Worlds and Doing the Right Thing: Morality, Ethics, and Civic Engagement -- Internet Use and Well Being: Physical and Psychological Effects -- Technology and Health: Using the Internet for Wellness and Illness -- When is it Too Much? Excessive Internet Use and Addictive Behavior -- The Darker Sides of the Internet: Violence, Cyber Bullying, and Victimization -- Promoting Positive and Safe Digital Worlds: What Parents and Teachers Can Do to Empower Youth -- Adolescents' Digital Worlds: Conclusions and Future Steps.
Electronic reproduction.
Keywords: Mass media and youth; Digital media -- Social aspects; Electronic books